Effectiveness of Roleplay Video Method in Teaching Communication Skills for Undergraduate Medical Students in Pharmacology in Indian Medical School - Volabailu, Ravichandra; Acharya, Swathi; Mohan, Venkatesh Krishna; Holla, Rajendra (Journal of Health and Allied Sciences NU, 2021)
Background Communication is an important skill to be honed and applied by Indian medical graduate, as per revised regulations on Graduate Medical Education 2019. The objective of the present study was to evaluate the effectiveness of roleplay video demonstration in teaching communication skills to students using standard pharmacology drug prescription scenarios.Materials and Methods In this study, 136 students were divided into three batches, and in each batch, they were paired as a group of one doctor and patient and were asked to perform a roleplay of doctor-patient communication to a standard drug prescription case scenario. Communication skills of the simulated doctor were assessed before and after the administration of standard roleplay video, using modified Kalamazoo consensus statement by both the patient (peer evaluation) and the doctor (self-assessment). The effectiveness of roleplay was evaluated by comparing the total score before and after the roleplay demonstration using the Wilcoxon signed rank test. The difference between the scores of self-evaluation and peer evaluation was tested using Mann–Whitney U test.Results The communication skills score of after intervention-before intervention (p = 0.001) showed 59 positive ranks and 36.64 mean rank among patient group and 61 positive ranks and 36.74 mean rank among doctors' group, indicating there was a significant improvement in communication.Conclusion Roleplay video demonstration improved the communication skills of students in the pharmacology practical class session. It helped in the active participation of the students and was appreciated by the majority of the students.
Keywords: roleplay; communication; pharmacology; kalamazoo consensus statement